Health Versus Economy: Lockdown Controversy Coverage in Indonesian Online News Platforms - Ardhanareswari Avianti Handoko (ULTIMA Comm, 2021)
Coronavirus Disease 2019 (COVID-19) pandemic has urged several countries to take an extreme measurement by imposing a lockdown policy to control the spread of the virus. Generally approved, the action might have several negative effects, primarily on economic aspects. Utilizing qualitative framing analysis, the study investigates how three national online economic and business media platforms, namely Kontan.co.id, Bisnis.com, and CNBCIndonesia.com, apply news frames to cater the lockdown-related issues to the public. The study identified four news frames: conflict, attribution of responsibility, economic consequences, and human interest. It appears that the ‘conflict frame' is heavily used to portray lockdown policy as an ‘arena of war' between health and economic interest. Keywords: COVID-19 Impacts, Economic and Business Media, Lockdown, Qualitative Framing Analysis